Letter - Heanor & District Local Labour Party and Trades Council, 7 May 1926 (Heanor)
1926-05-07 "Letter - Heanor & District Local Labour Party and Trades Council, 7 May 1926" [g0361001.jpg], 7 May 1926, Heanor & District Local Labour Party and Trades Council Local Organisation